Radon and thoron study in areas of elevated background radiation in Palong, Segamat, Johor - Abd. Wahab, Nur Amira (2015)
The study aims to present data on indoor and outdoor radon and thoron concentrations in areas of elevated background radiation in Palong, Segamat, Johor. The chosen area has the highest gamma background radiation in Johor. The measurements of equilibrium equivalent concentration of radon (EECRn) and thoron (EECTn) were carried out for periods of 12 hours from 7.00 am until 7.00 pm by using electronic radon dosimeter; DOSEman PRO. Terrestrial gamma radiations were measured and soil samples were collected in the area where radon and thoron monitoring took place. The results of radon and thoron concentrations were divided into three time intervals; morning (7.00 am – 11.00 am), afternoon (11.00 am – 3.00 pm) and evening (3.00 pm – 7.00 pm). The values of indoor and outdoor EECRn varied from 2.6 to 69.3 Bq m-3 and 0.4 to 48.2 Bq m-3 respectively. While for thoron, the values varied from 0 to 20.6 Bq m-3 and 0 to 27.5 Bq m-3 respectively. Indoor and outdoor gamma dose rates varied from 169 to 397 nGy h-1 and 81 to 1007 nGy h-1 respectively. The concentrations of uranium, thorium and potassium in soils were 20.7 to 967.3 Bq kg-1, 24.9 to 1003.8 Bq kg-1 and 4.5 to 4073.2 Bq kg-1 respectively. The populations in this area received annual effective dose between 0.54 mSv yr-1 to 7.52 mSv yr-1 due to terrestrial gamma and radon/ thoron exposure. The radiation dose is still within the normal range of 1-10 mSv yr-1 as stated by International Commission on Radiological Protection (ICRP).